Literary Parallels: Galaktion Tabidze and Luis de Camoens - Sikharulidze, Natia (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2022)
The paper analyses Galaktion Tabidze’s works that evince closeness to the Lusiads, the masterpiece of Luis de Camoens. The exploration of the diaries and autographs of Galaktion’s works revealed that the interest of the Ge- orgian poet in Portuguese literature is much more significant than it seems. Mo- reover, it turns out that G. Tabidze’s two verses are written based on a creative impulse received through the poem The Lusiads by Luis de Camoens, a classic poet of Portuguese literature. The Georgian poet expresses his thoughts about Camoens’ lines, Portuguese literature and culture through allusions. In this article, two verses by Galaktion which reveal a connection to The Lusiads are analyzed. The re-establishment of the genetic connection between the verses by Ga- laktion and The Lusiads by Luis de Camoens is an important fact because until now this kind of closeness between the Georgian and Portuguese literature has no t been observed.